2008
DOI: 10.1542/peds.2008-0770
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Children With Congenital Cytomegalovirus Infection in Relation to the Maternal Trimester in Which the Maternal Primary Infection Occurred

Abstract: Hearing loss seemed more common in infants with congenital cytomegalovirus infection who were born to women who experienced a primary cytomegalovirus infection in the first trimester of pregnancy than when infection took place later in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 19 publications
4
61
1
Order By: Relevance
“…Not only is the rate of abnormal outcome higher but the sequelae are more severe. 12,14,15 In fetuses confirmed to be infected, the risk of adverse perinatal outcome ranges from 20% to 45% for first trimester infections to 6% to 17% for second trimester infections. 12,[16][17][18] However, much of the existing literature is affected by methodological limitations and bias, and the wide range of adverse outcome is not helpful in prenatal counseling.…”
Section: Prediction Of Perinatal Outcome By Timing Of Maternal Infectmentioning
confidence: 99%
“…Not only is the rate of abnormal outcome higher but the sequelae are more severe. 12,14,15 In fetuses confirmed to be infected, the risk of adverse perinatal outcome ranges from 20% to 45% for first trimester infections to 6% to 17% for second trimester infections. 12,[16][17][18] However, much of the existing literature is affected by methodological limitations and bias, and the wide range of adverse outcome is not helpful in prenatal counseling.…”
Section: Prediction Of Perinatal Outcome By Timing Of Maternal Infectmentioning
confidence: 99%
“…A small study reported by Foulon et al [7] in 2008 related sensorineural hearing impairment in cCMV-infected children to the trimester of maternal primary CMV infection. They found 4 (80 % ) of fi ve cCMV-infected children with hearing impairment in the group of mothers with primary CMV infection in the fi rst trimester.…”
Section: Multinomial Groupmentioning
confidence: 97%
“…The most frequent congenital infection is CMV, as vaccines have reduced the incidence of rubella, mumps, and measles. Congenital CMV infection prevalence is estimated in about 0.64% children at birth [19] . It can be a primary or a recurrent infection; only 10% of infected children are symptomatic at birth, and hearing loss may be present in about half of the cases.…”
Section: Peri-and Post-natal Hearing Lossmentioning
confidence: 99%
“…It can be a primary or a recurrent infection; only 10% of infected children are symptomatic at birth, and hearing loss may be present in about half of the cases. CMV-related sensorineural hearing defect may be of mild-moderate degree, mono-or bilateral, typically fluctuating and, for most of the cases, with a delayed onset [18][19][20][21][22] . Also, many cases of idiopathic hearing loss in children with a late diagnosis are consequences of an unknown congenital CMV infection.…”
Section: Peri-and Post-natal Hearing Lossmentioning
confidence: 99%